Search for Higgs boson pair production in the bb [bar] WW [star] decay mode at √s=13TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Jongmanns, Jan; Kolb, Mathis; Kugel, Andreas; et al. (Journal of high energy physics, 2019)
A search for Higgs boson pair production in the bb¯¯WW∗bb¯WW∗ b\overline{b}WW^{*} decay mode is performed in the bb¯¯ℓνqqbb¯ℓνqq b\overline{b}\mathit{\ell ν qq} final state using 36.1 fb−1 of proton-proton collision data at a centre-of-mass energy of 13 TeV recorded with the ATLAS detector at the Large Hadron Collider. No evidence of events beyond the background expectation is found. Upper limits on the non-resonant pp → HH production cross section of 10 pb and on the resonant production cross section as a function of the HH invariant mass are obtained. Resonant production limits are set for scalar and spin-2 graviton hypotheses in the mass range 500 to 3000 GeV. Open image in new window
The ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Bolz, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, J. Jongmanns, M. Kolb, A. Kugel, F. Napolitano, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, S.M. Weber, M. Wessels, X. Yue [und weitere]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel steht der zweite Buchstabe b in bbWW* mit einem Oberstrich
b mit Oberstrich wird in der Physik als "b bar" ausgesprochen, in Latex geschrieben als "overline b"
Im Titel wird "star" als griechischer Buchstabe dargestellt